Stress and Academic Procrastination in Incoming University Students (Docentes 2.0 Journal, 2026)
The start of university life is a significant transitional stage that brings with it greater demands and goals. The accumulation of assignments and assessments can overwhelm students' organizational skills, leading to academic overload. This, coupled with the pressure to perform well, increases stress and encourages procrastination, negatively impacting their performance and well-being. The objective of this study was to determine the relationship between stress and academic procrastination in incoming students at the National Technological University of Lima South (UNTELS). Research was conducted within the positivist paradigm, using a hypothetical-deductive method, a quantitative approach, and a non-experimental, correlational, cross-sectional design, with a sample of 153 students. To compare these study variables, the Systemic Cognitive Inventory (SISCO) and the Academic Procrastination Scale (EPA) were used. The results show a strong, direct, and significant positive correlation between stress and academic procrastination (p=0.782, p-value
Keywords: Academic stress; academic procrastination; university freshmen